Intermodal integration of large volume air cargo - Guenov, Marin D. (Cranfield University, 2006)
Proposed is a novel air freight concept for intermodal container transport. The aim is to utilise the standardised (ISO) 20 and 40 foot containers currently in operation. Instead of a completely new, purpose built aircraft which would be too expensive, the baseline airframe considered is the planned Airbus freight configuration, A380-800F. Preliminary calculations show that an aircraft with the capacity and dimensions of A380 can carry up to six 40’ or up to fourteen 20’ containers as well as combinations of these, depending on load density. Considered are the necessary aircraft modifications, the cost and weigh implications, and also the efficiency of the concept. The conclusion is that such a modification may reduce the payload of the aircraft by about 6%, but the time savings can be very significant. Furthermore, the seamless integration of ISO 20’ and 40’ containers has the potential to radically change the air cargo business as it could become an integral part of the global manufacturing supply chain. This would extend the traditional air cargo market from perishables, clothing, high value and fragile items to components and even intermediate materials, given economies o
Keywords: Intermodal Transport; Air Cargo; Container Transport; Logistics